Oxygen Consumption of White Shrimp (Litopenaeus vannamei) and Model of Oxygen Management in Intensive Culture Pond - T. Budiardi; T. Batara; D. Wahjuningrum (Jurnal Akuakultur Indonesia)
This study was conducted to determine oxygen consumption level of white shrimp (Litopenaeus vannamei) and the model of oxygen management in intensive culture pond.   Shrimp in weight of 5 gram were maintained in 20 liter of water in density 6 tails/container.  Water quality was measured every 2 hours for 6 hours.  Other experiments were done using shrimp in weight of 8, 10, 12 and 15 gram per tail, in density 4 tails/container.  The results of study showed that oxygen consumption levels of white shrimp was higher after feeding than before feeding.  Oxygen consumption levels of smaller shrimp were higher than that of bigger shrimp.  Regression model of oxygen consumption levels before and after feeding were linear. Correlation between oxygen consumption and shrimp weight reached 92.5%.